2002
DOI: 10.1116/1.1495507
|View full text |Cite
|
Sign up to set email alerts
|

Two-directional N2 desorption in thermal dissociation of N2O on Rh(110), Ir(110), and Pd(110) at low temperatures

Abstract: Two-directional N 2 desorption was found in N 2 O dissociation on Rh͑110͒, Ir͑110͒, and Pd͑110͒ below 160 K by angle-resolved thermal desorption. N 2 O(a) is mostly dissociated during heating procedures, emitting N 2 (g) and leaving O(a). N 2 showed four desorption peaks in the temperature range of 110-200 K. One of them commonly showed a cosine distribution, whereas the others sharply collimated off the surface normal in the plane along the ͓001͔ direction. The collimation angle was about 70°on Rh͑110͒, 65°on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…In the pathway through the N 2 O intermediate on Rh(110), desorbing N 2 is expected to collimate at 30−70° off the surface normal because such large collimation angles were observed in the N 2 O decomposition. However, neither inclined N 2 desorption nor N 2 O production became noticeable up to about 1 × 10 -4 Torr of NO. N 2 desorption always collimated along the surface normal, suggesting that the associative process is predominant .…”
Section: Introductionmentioning
confidence: 99%
“…In the pathway through the N 2 O intermediate on Rh(110), desorbing N 2 is expected to collimate at 30−70° off the surface normal because such large collimation angles were observed in the N 2 O decomposition. However, neither inclined N 2 desorption nor N 2 O production became noticeable up to about 1 × 10 -4 Torr of NO. N 2 desorption always collimated along the surface normal, suggesting that the associative process is predominant .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nitrogen molecules produced on some fcc (110) surfaces were observed to desorb in inclined bidirectional lobes in a plane in the [001] and [001̄] directions. The processes investigated so far are the thermal dissociation of N 2 O on Pd, Rh, and Ir, the thermal decomposition of NO on Pd, ,,, and the steady-state NO + CO reaction on Pd. , By using isotope tracers, Ikai and Tanaka clearly showed that, on Pd(110), desorbing N 2 molecules, from the recombination reaction of 2N(a) → N 2 (g) collimated sharply along the surface normal, whereas N 2 from NO decomposition desorbed in an inclined direction . Haq and Hodgson suggested that the inclined desorption of N 2 was due to locally reconstructed or corrugated patches induced by N 2 O adsorption .…”
Section: Introductionmentioning
confidence: 99%
“…The orientation of adsorbed N 2 O just before the decomposition is thus inferred from the spatial distribution of N 2 desorption, 1 in which oxygen of N 2 O is bound to a Rh atom. 2 The distribution of N 2 in thermal N 2 O decomposition has been already reported on Pd(110), [3][4][5] Rh(110), [6][7][8][9] Ir(110), 10 and Rh(100) (Ref. 6) under temperature programmed desorption (TPD), pressure jump/drop decomposition, and/or steady-state reduction conditions.…”
Section: Introductionmentioning
confidence: 81%